2022
DOI: 10.3390/toxins14010044
|View full text |Cite
|
Sign up to set email alerts
|

Significant Long-Lasting Improvement after Switch to Incobotulinum Toxin in Cervical Dystonia Patients with Secondary Treatment Failure

Abstract: Under continuous long-term treatment with abo- or onabotulinum toxin type A (BoNT/A), ~10 to 15% of patients with cervical dystonia (CD) will develop neutralizing antibodies and reduced responsiveness over an ~10-year treatment period. Among the botulinum neurotoxin type A preparations so far licensed for CD, incobotulinum toxin A (incoBoNT/A; Xeomin®) is the only one without complex proteins. Whether CD patients with treatment failure under abo- or onaBoNT/A may still respond to incoBoNT/A is unknown. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Additional strengths include that most of the incorporated studies were placebo-controlled for the first injection cycle, data were obtained over multiple incobotulinumtoxinA injection cycles and the analyses were performed on a background of stable antispastic medications (centrally acting muscle relaxants, benzodiazepine) and physical/occupational therapy. Using a multipattern treatment approach, incobotulinumtoxinA produced effective improvements in QoL-related outcomes, a finding that should be considered along with the well-established safety profile and low immunogenicity profile of incobotulinumtoxinA [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Furthermore, the mixed etiology of spasticity evident in this study may make the findings applicable to a wider range of patients, although most patients had poststroke spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Additional strengths include that most of the incorporated studies were placebo-controlled for the first injection cycle, data were obtained over multiple incobotulinumtoxinA injection cycles and the analyses were performed on a background of stable antispastic medications (centrally acting muscle relaxants, benzodiazepine) and physical/occupational therapy. Using a multipattern treatment approach, incobotulinumtoxinA produced effective improvements in QoL-related outcomes, a finding that should be considered along with the well-established safety profile and low immunogenicity profile of incobotulinumtoxinA [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Furthermore, the mixed etiology of spasticity evident in this study may make the findings applicable to a wider range of patients, although most patients had poststroke spasticity.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Moreover, a recent study found significant long‐lasting improvement after switch to A/Inco for cervical dystonia patients with secondary treatment failure. 19 In addtion to the CPs, the excipients in different BTX‐As might be the reason for the enhancement of paralytic efficacy, and studies had reported that the stabilizer such as human serum albumin could result in enhanced BTX‐A activity in the mLD50 assay. 12 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…16 Except from this, CPs played a vital role in the antibody-induced failure of the BTX therapy, probably via increasing the BTX-A antigenicity. 17 19 In addtion to the CPs, the excipients in different BTX-As might be the reason for the enhancement of paralytic efficacy, and studies had reported that the stabilizer such as human serum albumin could result in enhanced BTX-A activity in the mLD50 assay. 12,20,21 There are some limations in this study.…”
Section: Gastrocnemius Muscle Strength Meanmentioning
confidence: 99%
“…Patients were classified as patients with primary treatment failure (PTF) when their improvement during the entire course of treatment (assessed using the TSUI scale [19]) was lower than 3 points. Patients were classified as secondary non-responders (STF) when they experienced an improvement of at least 3 TSUI points, followed by a systematic worsening of at least 2 TSUI points over at least two treatment cycles during their course of treatment (for details of the definition of secondary non-responders, see [22]). Two patients were primary non-responders (open symbols in Figures 1 and 2), and four patients were secondary non-responders (full black symbols in Figures 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…A mean BTSUI of 3.75 was observed after a treatment period of 1354 days (corresponding to 15 injections), with a mean dose of 843 U aboBoNT/A (=281 uDU). The mean BTSUI was 3.83 in a group of CD patients exclusively treated with 321 U onabotulinum neurotoxin type A(onaBoNT/A; Botox ® ) over 1085 days (corresponding to 12 injections), and was 1.71 in a group of CD patients exclusively treated with 267 U incoBoNT/A over 920 days (corresponding to 10 injections) [22]. Having reached its best value, the TSUI score slowly increases again when the dose of BoNT/A is not increased.…”
Section: Reasons For the Excellent Outcome In The Present Cohortmentioning
confidence: 99%